Jazz’s little brother: The origins of the Spanish blues scene - Pedro, Josep (Jazz Research Journal, 2020)
Drawing on ethnographic, archival and analytical research, this article examines the origins of the blues scene in Spain. A complex, heterogeneous period that spans from the 1930s to the 1980s, the origins are explored diachronically in relation to four primary aspects: the reception of blues through the growing jazz scene; the national production of blues and blues-related music within the frameworks of jazz, rock and flamenco; the transformative contributions of foreign musicians and cultural producers; and the ultimate development of specialized blues bands that represent a more ‘purist’ appropriation of blues as an autonomous genre. In this process, the article provides a historical overview and a musical mapping of blues in Spain, revealing its unique contribution to modernity as a meaningful, porous common ground between the hegemonic jazz and rock music cultures.